Inovasi Karier Digital: Integrasi Gamifikasi Dalam Program Bimbigan Dan Konseling Komprehensif - Hardiyanti, Nita Qisthi; Prasetya, Akhmad Fajar; Muarifah, Alif; Saputra, Wahyu Nanda Eka (Jurnal Ilmu Bimbingan dan Konseling, 2025)
The development of digital technology has driven the need for innovation in comprehensive guidance and counseling services, particularly in facilitating students' career development more effectively and engagingly. This study examines the integration of gamification into a comprehensive guidance and counseling program as a strategy to increase students' motivation, engagement, and understanding of career planning in the digital era. Through the implementation of game elements such as points, levels, challenges, and instant feedback, the program is designed to create a more interactive and personalized learning experience. The study results indicate that gamification can increase active participation, strengthen understanding of career concepts, and encourage the development of 21st-century competencies such as creativity, collaboration, and digital literacy. This integration also helps counselors monitor student progress more objectively and systematically. Thus, gamification is a potential innovative approach to strengthen the effectiveness of career guidance and counseling services in a technology-based educational context.